Enhancing Elementary School Students’ Understanding of Fraction Concepts through Fraction Tower Challenge Game - Fuadi, Fawwaz; Fajri, Moh. Dawil Al Fazary; Andika, Putra; Wahab, Abdul; Ummah, Fiena Saadatul (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
One of the essential competencies in elementary mathematics education is students’ conceptual understanding of fractions. However, many students continue to experience difficulties in learning fractions because the material is often presented in a monotonous and abstract manner. This study aimed to improve elementary school students’ conceptual understanding of fractions through the implementation of the Fraction Tower Challenge, an educational game-based learning medium. The study employed a Classroom Action Research (CAR) design consisting of two cycles, each involving the stages of planning, implementation, observation, and reflection. The participants were 18 third-grade elementary school students. Data were collected through classroom observations, documentation, and written tests administered as pre-tests and post-tests in the form of essay questions. The findings indicated that the implementation of the Fraction Tower Challenge significantly improved students’ conceptual understanding of fractions. The comparison between pre-test and post-test scores in the first cycle demonstrated a substantial improvement, while the second cycle showed further progress, although the increase was less pronounced than in the first cycle. Overall, the Fraction Tower Challenge enabled students to understand fraction concepts in a more enjoyable, visual, and concrete way.